2002
DOI: 10.1002/bip.10051
|View full text |Cite
|
Sign up to set email alerts
|

On residues in the disallowed region of the Ramachandran map

Abstract: An analysis of the occurrence of nonglycyl residues in conformations disallowed in the Ramachandran plot is presented. Ser, Asn, Thr, and Cys have the highest propensities to exhibit such conformations, and the branched aliphatic residues the lowest. Residues cluster in five regions and there are some trends in the types of residues and their side-chain conformations (chi(1)) occupying these. Majority of the residues are found at the edge of helices and strands and in short loops, and are involved in different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
67
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(72 citation statements)
references
References 25 publications
5
67
0
Order By: Relevance
“…7. 94 In the aqueous region of the simulation box, the φ and ψ angles of NAFA, NAYA, and NATA are grouped into three areas: the large region with negative ψ angles represents α-helical type conformations, the region in the top left corner-β-sheet and extended structures, and the small region in-between the C 7eq conformer characteristic of dipeptides. 95 As the dipeptides move from solution to interface, the probabilities in the α and β regions decrease, while that of C 7eq increases.…”
Section: Backbone Conformationsmentioning
confidence: 99%
“…7. 94 In the aqueous region of the simulation box, the φ and ψ angles of NAFA, NAYA, and NATA are grouped into three areas: the large region with negative ψ angles represents α-helical type conformations, the region in the top left corner-β-sheet and extended structures, and the small region in-between the C 7eq conformer characteristic of dipeptides. 95 As the dipeptides move from solution to interface, the probabilities in the α and β regions decrease, while that of C 7eq increases.…”
Section: Backbone Conformationsmentioning
confidence: 99%
“…Gunasekaran et al (42) found such conformations in the second position (iϩ1) of perfect type IIЈ ␤-turns. In a follow-up on this work, Pal and Chakrabarti (43) reported that such residues (in their nomenclature, "region II" residues) are "common in the first position of 3 10 -helices, which in the majority of cases lead into ␣-helices." As type IIЈ ␤-turns are essentially short 3 10 -helices, the results of Gunasekaran et al and Pal and Chakrabarti are perfectly consistent.…”
Section: Discussionmentioning
confidence: 92%
“…This cluster falls into one of the six clusters identified in the earlier analyses. 51,52 The backbone conformation of the residues in this cluster corresponds to the i+1 position of a type II' β-turn. [53][54][55] Incidentally, the histidinecontaining phosphocarrier protein also has a disallowed residue (Ala16) falling in this cluster.…”
Section: Are Ramachandran Disallowed Conformations Frequent In Class mentioning
confidence: 99%